Studi Literatur Keterkaitan Pembangunan Ekonomi dengan Kualitas Sumber Daya Manusia di Kota Medan - Abdul Malik Karim Amrullah; Feri Arifin; Mhd. Rofi Febrian; M. Nabil Nasution (STIKes Ibnu Sina Ajibarang, 2025)
This study examines the relationship between economic development in Medan City and the quality of human resources (HR). Medan, as the third largest city in Indonesia, needs to optimise the quality of human capital to reach its full economic potential. Four previous studies were analysed to understand the influence of human resource quality on urban economic dynamics. The results showed that increased organisational commitment, technology utilisation, and human resource capacity development are positively correlated with improved financial statement quality and economic growth. In addition, sustainable management of natural resources also plays a role in promoting economic growth. This study emphasises the importance of government intervention in improving education standards and HR competencies to create jobs and reduce unemployment. Thus, Medan City's economic development planning should be integrative and sustainable with a focus on improving the quality of human resources and optimising local potential as the main foundation of community welfare.